Facultad del notario en los divorcios por mutuo consentimiento. - Miura Ochoa, John André (2013)
This situation affects the parties, and that without the aforementioned limiting spouses could attend a notary to arrange a divorce by mutual consent, provided that the obligations of parents towards their minor children are settled, as is It occurs in close international law as Colombia, Cuba, and Peru.